Increasing Activities and Student Learning Outcomes with the Project-Based Learning Model in the Thematic Learning Theme of Our Friends in Class V SDN 101911 Sidodadi - Audia, Rizki; Hidayat, Hidayat (Universitas Trunojoyo Madura, 2023)
This study aims to increase student activity and learning outcomes in thematic learning on the theme of our friend's environment in class V SD Negeri 101911 Sidodadi. This research is a Class Action Research (CAR) using the Kemmis and Mc model. Taggart. This research is descriptive qualitative by using a qualitative approach which is strengthened by a quantitative approach.The results showed that there was an increase in activity and student learning outcomes in thematic learning by using project based learning learning models. The results of the research using the project based learning model were carried out well, as evidenced by the results of teacher observations in cycle I obtaining a percentage of 62.5% (good enough), cycle II increased to 80.3% (good), and cycle III increased to 91, 0% (very good). The results of observations of student learning activities in cycle I obtained a percentage of 32.2% (less active), experienced an increase in cycle II and cycle III, namely 57.9% (quite active) and 70.8% (active). In the learning outcomes of students in the first cycle classically only reached 49.1% of the criteria were not good. In cycle II, classical learning outcomes increased to 66.2% with good enough criteria. In cycle III, student learning outcomes classically experienced an increase again, namely, reaching 77.5% with good criteria. Thus the learning model of project based learning in thematic learning on the theme of our friend's environment in class V SD Negeri 101911 Sidodai can increase student activity and learning outcomes.